Neoproterozoic evolution and Cambrian reworking of ultrahigh temperature granulites in the Eastern Ghats Province, India. (28th October 2018) - Mitchell, Ruairidh J.; Johnson, Tim E.; Clark, Chris; Gupta, Saibal; Brown, Michael; Harley, Simon L.; Taylor, Richard
Abstract: The time‐scales and P–T conditions recorded by granulite facies metamorphic rocks permit inferences about the geodynamic regime in which they formed. Two compositionally heterogeneous cordierite–spinel‐bearing granulites from Vizianagaram, Eastern Ghats Province (EGP), India, were investigated to provide P–T– time constraints using petrography, phase equilibrium modelling, U–Pb geochronology, the rare earth element composition of zircon and monazite, and Ti‐in‐zircon thermometry. These ultrahigh temperature (UHT) granulites preserve discrete compositional layering in which different inferred peak assemblages are developed, including layers bearing garnet–sillimanite–spinel, and others bearing orthopyroxene–sillimanite–spinel. These mineral associations cannot be reproduced by phase equilibrium modelling of whole‐rock compositions, indicating that the samples became domainal on a scale less than that of a thin section, even at UHT conditions. Calculation of the P–T stability fields for six compositional domains within which the main rock‐forming minerals are considered to have attained equilibrium suggests peak metamorphic conditions of ~6.8–8.3 kbar at ~1, 000°C. In most of these domains, the subsequent evolution resulted in the growth of cordierite and final crystallization of melt at an elevated (residual) H2 O‐undersaturated solidus, consistent with <1 kbar of decompression. Concordant U–Pb ages obtained by SHRIMP from zircon (spread 1, 050–800 Ma) and monazite (spread 950–800 Ma) demonstrate that crystallization of these minerals occurred during an interval of c . 250 Ma. By combining LA‐ICP‐MS U–Pb zircon ages with Ti‐in‐zircon temperatures from the same analysis sites, we show that the crust may have remained above 900°C for a minimum of c . 120 Ma between c . 1, 000 and c . 880 Ma. Overall, the results suggest that, in the interval 1, 050 to 800 Ma, the evolution of the Vizianagaram granulites culminated with UHT conditions from c . 1, 000 Ma to c . 880 Ma, associated with minor decompression, before further zircon crystallization at c . 880–800 Ma during cooling to the solidus. However, these rocks are adjacent to the Paderu–Anantagiri–Salur crustal block to the NW that experienced counterclockwise P–T–t paths, and records similar UHT peak metamorphic conditions (7–8 kbar, ~950°C) followed by near‐isobaric cooling, and has a similar chronology during the Neoproterozoic. The limited decompression inferred at Vizianagaram may be explained by partial exhumation due to thrusting of this crustal block over the adjacent Paderu–Anantagiri–Salur crustal block. The residual granulites in both blocks have high concentrations of heat‐producing elements and likely remained hot at mid‐crustal depths throughout a period of relative tectonic quiescence in the interval 800–550 Ma. During the Cambrian Period, the EGP was located in the hinterland of the Denman–Pinjarra–Prydz orogen. A later concordant population of zircon dated at 511 ± 6 Ma records crystallization at temperatures of ~810°C. This age may record a low‐degree of melting due to limited influx of fluid into hot, weak crust in response to convergence of the Crohn craton with a composite orogenic hinterland comprising the Rayner terrane, EGP, and cratonic India.